2009
DOI: 10.1007/s11433-009-0205-z
|View full text |Cite
|
Sign up to set email alerts
|

Heavy-ion fusion and scattering with Skyrme energy density functional

Abstract: In our recent studies, an empirical barrier distribution was proposed for a unified description of the fusion cross sections of light and medium-heavy fusion systems, the capture cross sections of the reactions leading to superheavy nuclei, and the large-angle quasi-elastic scattering cross sections based on the Skyrme energy-density functional approach. In this paper, we first give a brief review of these results. Then, by examining the barrier distributions in detail, we find that the fusion cross sections d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 58 publications
(87 reference statements)
1
37
0
Order By: Relevance
“…For reaction 238 U(n, f) at low incident energies (E n ≤ 6.5 MeV), the positions A 1 and A 2 are obtained from the nucleus-nucleus driving potential of the fissile nucleus 239 U [22,23]. With .…”
Section: The Combination Methods and The Potential Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…For reaction 238 U(n, f) at low incident energies (E n ≤ 6.5 MeV), the positions A 1 and A 2 are obtained from the nucleus-nucleus driving potential of the fissile nucleus 239 U [22,23]. With .…”
Section: The Combination Methods and The Potential Parametersmentioning
confidence: 99%
“…(3). Based on the nucleus-nucleus potential with the Skyrme energy-density functional [22,23], the driving potentials of these fissile Fig. 3.…”
Section: The Combination Methods and The Potential Parametersmentioning
confidence: 99%
“…(1) will be simplified as the three harmonic-oscillator functions [1]. The positions A 1 and A 2 are obtained from the nucleus-nucleus driving potential of the fissile nucleus 233 Th [1,15,16]. With increasing the incident neutron energy, the excitation energy of the compound nucleus will become higher, and a few neutrons will be evaporated before scission.…”
Section: Fission Potential and Its Parametersmentioning
confidence: 99%
“…By examining the barrier distributions in detail, it is found that the fusion cross sections depend more strongly on the shape of the left side of the barrier distribution while the quasi-elastic scattering cross sections depend more strongly on the right side [63]. Furthermore, by combining these studies and the HIVAP calculations for the survival probability, the formation probability of the compound nucleus is deduced from the measured evaporation residue cross sections for cold and hot fusion reactions.…”
Section: Synthesis Of Superheavy Elements (She) Via Heavy Ion Fusion mentioning
confidence: 99%
“…The Cooling Storage Ring of Heavy Ion Research Facility in Lanzhou (HIRFL-CSR) [8][9][10] was completed in 2007, which aims at the exploration of physics with radioactive ion beams, including the structure of unstable nuclei, isospin dependence of nuclear matter, heavy-ion fusion reactions, superheavy nuclei synthesis, hadronic physics, physics of high-energy density matter, physics of highly charged ions, and applications. Recently direct mass measurements of short-lived A = 2Z −1 nuclides 63 Ge, 65 As, 67 Se, and 71 Kr were carried out at HIRFL-CSR and these results have a great impact on nucleosynthesis in the rp process [11][12][13][14]. Shanghai Synchrotron Radiation *Corresponding author (email: egzhao@mail.itp.ac.cn) Facility (SSRF) [15], which was finished and commissioned in April 2009, and Daya Bay nuclear power complex in China [16] also provides many opportunities for nuclear science.…”
mentioning
confidence: 99%